Effect of Economic Growth on Unemployment Rate in Indonesia - Dikko Alrakhman; Didik Susetyo; Taufiq Taufiq; Azwardi Azwardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and empirically prove the effect of economic growth and wages provincial minimum (UMP) to the unemployment rate in Indonesia econometric model multiple regression for panel data. Results the study found that economic growth was proven to have a negative (decreasing) and significant effect on the unemployment rate. Meanwhile, the provincial minimum wage is proven to have a positive (increasing) and significant effect on the unemployment rate. This research has limitations, that is, using only two independent variables (economic growth and the provincial minimum wage) so that there are other factors or variables outside the model that can also affect the dependent variable (unemployment rate). The contribution given from this research is as input as well as evaluation for interested parties in making policies (Government and Regional Government) so that they can produce more targeted policies in an effort to reduce unemployment rates, especially for Regional Governments in Indonesia.